2005
DOI: 10.4049/jimmunol.175.1.112
|View full text |Cite
|
Sign up to set email alerts
|

Coimmunization with an Optimized IL-15 Plasmid Results in Enhanced Function and Longevity of CD8 T Cells That Are Partially Independent of CD4 T Cell Help

Abstract: DNA vaccines are a promising technology for the induction of Ag-specific immune responses, and much recent attention has gone into improving their immune potency. In this study we test the feasibility of delivering a plasmid encoding IL-15 as a DNA vaccine adjuvant for the induction of improved Ag-specific CD8+ T cellular immune responses. Because native IL-15 is poorly expressed, we used PCR-based strategies to develop an optimized construct that expresses 80-fold higher than the native IL-15 construct. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
151
0
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 173 publications
(161 citation statements)
references
References 67 publications
7
151
0
3
Order By: Relevance
“…Notably, the loss of IFN-␥-producing CD8 ϩ T cells specific to HIV Ags has been observed in HIV Gag DNA-immunized CD4 knockout mice. These data support the need for CD4 ϩ T cells during priming for generation of functional CD8 ϩ effector cells (38). In our study, we found that the induced CD4 ϩ T cell response in mice was below detectable level; this may explain in part the presence of a high proportion of CD8 ϩ T cells that functionally were not in the immediate IFN-␥ effector phenotype.…”
Section: Discussionsupporting
confidence: 82%
“…Notably, the loss of IFN-␥-producing CD8 ϩ T cells specific to HIV Ags has been observed in HIV Gag DNA-immunized CD4 knockout mice. These data support the need for CD4 ϩ T cells during priming for generation of functional CD8 ϩ effector cells (38). In our study, we found that the induced CD4 ϩ T cell response in mice was below detectable level; this may explain in part the presence of a high proportion of CD8 ϩ T cells that functionally were not in the immediate IFN-␥ effector phenotype.…”
Section: Discussionsupporting
confidence: 82%
“…It was reported that the effects of IL-7 as a genetic adjuvant have been known to be weaker and less effective than those of IL-15, a well-known and effective vaccine adjuvant [29]. In contrast to IL-7, nonlytic Fc fusion to IL-15 slightly increased, albeit insignificantly, the adjuvant effect of IL-15 on enhancing CD8 1 T-cell responses (Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Recent advances in immunology have shown that several types of molecules may be used as novel adjuvants to enhance immunogenicity of vaccines, such as cytokines, chemokines, Toll-like receptor ligands, and some costimulatory molecules [44][45][46][47]. Among these molecules, CD40L is attractive since it is one of the main mechanisms by which CD4 + T cells provide help to CTL and B cells [16,18,19,31].…”
Section: Discussionmentioning
confidence: 99%